2018
DOI: 10.21273/hortsci13154-18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Boron Omission and Foliar Fertilization on Nutrition Efficiency and Production of Cowpea

Abstract: Additional index words. Vigna unguiculata, plant nutrition, crop quality, nutrient management, sorbitolAbstract. This study aimed to evaluate the effects of boron (B) omission on cowpea nutrition and to compare the impact of foliar B fertilization with and without sorbitol on cowpea growth, nutritional status, and B uptake. Two trials using a completely randomized experimental design were conducted. During the first experiment, nutrient solution was provided without B (LB) and with B (+B) in 10 replicates. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, the foliar application of B resulted in a residual effect that benefited new leaves, corroborating the study of Wu et al (2019) with citrange. It was also observed that these treatments increased the total B concentration of new leaves (Table 1), reaching an adequate range for this species (21 to 35 mg kg −1 ) (Silva et al, 2018).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Therefore, the foliar application of B resulted in a residual effect that benefited new leaves, corroborating the study of Wu et al (2019) with citrange. It was also observed that these treatments increased the total B concentration of new leaves (Table 1), reaching an adequate range for this species (21 to 35 mg kg −1 ) (Silva et al, 2018).…”
Section: Discussionmentioning
confidence: 62%
“…Boron must be optimally absorbed in order to generate a significant response to its application in cowpea plants (Silva et al, 2018). In this sense, our study indicated that applying B via foliar spraying in association with growth media fertilization ( 10 B-L + B-S) resulted in a greater accumulation of this nutrient in plant organs compared with the control treatment without B supply (Figure 2).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations